(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
Science and technology have made a huge invasion in our lives. Since the beginning of this world, the intelligence of human beings has resulted in the growth of science and technology according to the interests and needs of humankind. The modern inventions of science and technology shall have serious impact on the law and the justice delivery system of any country. The evolution of science and technology has enabled law enforcement agencies to solve many apparently ‘cold crimes’, which have made people to associate forensic science with detection of crimes. The basic function of forensic technology is to assist in the administration of justice. DNA technology could be the greatest single advancement in the search of truth, conviction of the guilty and acquittal of the innocent since the advent of cross-examination. This technology has revolutionised the modes of investigation of violent crimes as a result of its precision in matching physical and biological evidence from a crime scene to either convict a perpetrator or vindicate a convicted offender. In essence, DNA evidence is rapidly becoming irrefutable proof of identification. The pace of using DNA technology in the worldwide justice delivery system is increasing. Despite the increase in the use of DNA technology, there is no legislation providing for general administration of the application of DNA technology in India. Although the Indian justice system has realised the importance of the DNA technology in safeguarding the sentinels of justice since its inception, it is serving as a helping hand to the justice system of the country. The law of the country is bound to change due to the revolutionary scientific changes. Hence, an effort must be made to better administer the application of the DNA fingerprinting, so that criminals can be convicted easily and more reliably.